A decision support system to facilitate collaborative supply of food cooperatives. Issue 14 (26th October 2021) - Fikar, Christian; Leithner, Magdalena
Abstract: Food cooperatives are gaining popularity due to consumers' desire to eat healthy and source locally. Mainly run by private citizens, such groups present an interesting additional income source to regional organic farmers. However, small order quantities and substantial logistics efforts challenge operations. To facilitate efficient and sustainable food transports from farms to food cooperatives, this work investigates impacts of collaborative logistics activities through the development of a simulation and optimization-based decision support system. Results of computational experiments considering fresh food transports in Austria highlight potentials of such joint activities. Particularly, if orders are infrequent and quantities small, collaboration results in a substantial reduction of travel distances and reduces the number of required vehicles. Nevertheless, delivered food quality may deteriorate as consolidating shipments results in longer travel durations as well as additional loading and unloading activities.